A mixed-methods investigation of an ecological momentary assessment protocol for cigarette-smoking youth: Psychometric properties and participant experiences - Suhaavi Kochhar; Hanneke Scholten; Dominique F Maciejewski; Michelle A Pingel; Maartje Luijten (Drug and Alcohol Dependence Reports)
Introduction: Ecological momentary assessment (EMA) is popular in smoking research to study time-varying processes and design just-in-time personalised cessation interventions. Yet, research examining the psychometric properties of EMA and user experiences with EMA protocols is lacking. We conducted a mixed-methods study to test the EMA component of a mobile intervention for middle to late-aged adolescents (16–20 years) who smoke cigarettes at least weekly. Method: Participants (N = 84) filled out global self-report measures at pre- and post-test, and reported their craving, mood, and smoking behaviour five times daily for seven days via their phones. We tested intra-class correlations, convergent validity, test-retest reliability, and multilevel internal consistency of the EMA items. Further, participants answered qualitative questions about their experiences with the EMA including the timing and frequency of assessments, clarity of individual items, and how it impacted their daily lives. Results: The EMA questionnaires showed good convergent validity and reliability. The average compliance rate was 77 %, and generally, participants evaluated the experience positively. While most participants rated the timing and frequency of EMA positively, some participants did not like that assessments expired after 1.5 h. Forty percent of participants also reported that they liked monitoring their smoking and mood. Conclusions: The use of EMA in our target group is feasible and had good compliance. The items used are suitable for researchers to use in future studies. We urge researchers to test the psychometric quality and feasibility of new EMA protocols before using them in confirmatory research.